Implementasi Metode MAUT dengan Menerapkan Pembobotan ROC Dalam Pemilihan Ketua Himpunan Mahasiswa - Jhiro Faran; Rima Tamara Aldisa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The election of the head of the student association is an important process in maintaining the sustainability and progress of the organization. However, determining the best association chairperson can be a complex and subjective task. Therefore, we need an effective decision support system to assist in the selection process. This study aims to develop a Decision Support System (DSS) using the Multi-Attribute Utility Theory (MAUT) method with ROC weighting in selecting the best association chairman. The MAUT method is one of the methods used to overcome complexity in decision making by considering several relevant attributes. The results of this study are expected to provide objective recommendations in the process of selecting the best chairman of the association. The results of this study using the MAUT method are with a value of 0.775 as the highest alternative chosen as chairman of the association. By utilizing the MAUT method, this system can assist the relevant election committee in obtaining better and more informed decisions. This proposed decision support system can also be used as a guide for other schools facing similar challenges in selecting association leaders